EBV-Positive Gastric Cancer: Current Knowledge and Future Perspectives - Sun, Keran; Jia, Keqi; Lv, Huifang; Wang, Sai-Qi; Wu, Yan; Lei, Huijun; Chen, Xiaobing (Frontiers in Oncology, 2020)
Gastric cancer is the fifth most common malignant tumor and second leading cause of cancer-related deaths worldwide. With the improved understanding of gastric cancer, a subset of gastric cancer patients infected with Epstein-Barr virus (EBV) has been identified. EBV-positive gastric cancer is a type of tumor with unique genomic aberrations, significant clinicopathological features, and a good prognosis. After EBV infects the human body, it first enters the incubation period where the virus integrates its DNA into the host and expresses the latent protein, and then affects the DNA methylation through miRNA under the action of the latent protein, which leads to the occurrence of EBV-positive gastric cancer. With recent developments in immunotherapy, better treatment of EBV-positive gastric cancer patients appears achievable. Moreover, studies have shown that treatment with immunotherapy has high effective rate in patients with EBV-positive gastric cancer. This review will summarize the research status of EBV-positive gastric cancer in recent years and indicate areas for improvement of clinical practice.